The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.18421/tem113-46
|View full text |Cite
|
Sign up to set email alerts
|

Digital Learning Research in the Last 30 Years: Important Role of Interactive Learning in Physics

Abstract: The aim is to analyze top 100 highest citations of digital learning research topics and the important role of interactive learning in physics in 1992-2021. This study uses bibliometric analysis and literature review. The trend of digital learning topics is increasing steadily, from 2014 to 2021. Digital learning shows an excellent contribution to physics learning. The important role of interactive learning in physics is to improve student learning outcomes, deepen understanding and make learning more interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…According to the study on students' digital literacy skills, problems were found from the future teachers in collecting information for the internet and social problems. Not many teachers used the data from comparative comparison to find causes before applying the data in the digital age for developing students to become digital citizens with good knowledge and analytical thinking, advanced technological skills, and self-assistance such as using interactive modules for digital literacy [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…According to the study on students' digital literacy skills, problems were found from the future teachers in collecting information for the internet and social problems. Not many teachers used the data from comparative comparison to find causes before applying the data in the digital age for developing students to become digital citizens with good knowledge and analytical thinking, advanced technological skills, and self-assistance such as using interactive modules for digital literacy [16,17].…”
Section: Introductionmentioning
confidence: 99%